A review of the Chinese species of the genus Picromerus Amyot and Serville, with description of a new species (Hemiptera: Heteroptera: Pentatomidae: Asopinae) - Zhao, Qing; Liu, Guoqing; Bu, Wenjun (Zootaxa, 2013)
Six species of the genus Picromerus Amyot and Serville from China were reported, in which, Picromerus elevatus sp. nov. fromYunnan province, was described as new to science. Drawings and photographs of genital characters, photo-graphs of imagoes in dorsal and ventral views, and some diagnostic characters were provided, together with a detailed key to the six species occurring inChina. The type specimens were deposited in theInstitute ofEntomology, Nankai Univer-sity,Tianjin,China, except noted.